Menghadapi Revolusi Industri 4.0: Personality Development Training untuk Meningkatkan Kesiapan Kerja Siswa SMK - Dian Dwi Nur Rahmah; Elda Trialisa Putri; Anindya Pinasthi Putri (JIP (Jurnal Intervensi Psikologi), 2021)
The industrial revolution 4.0 demands that human resources have quality in various aspects of life so that they can continue to compete in employment. Based on this, human resources must have work readiness in order to be able to face the changes that occur. The purpose of this study was to determine the effectiveness of personality development training as a step in increasing work readiness of students of SMK Negeri 5 Samarinda in facing the industrial revolution 4.0. This research uses one group pretest posttest design. The subjects involved in this study were 30 students of SMK Negeri 5 Samarinda. Data were collected using a work readiness scale. Data were analyzed using paired sample t-test. The results show that personality development training is effective in increasing the level of work readiness of students of SMK Negeri 5 Samarinda